Mourning and guilt in Ayer no mas by Andres Trapiello - Bender, Elzbieta (Romanica Olomucensia, 2019)
Andres Trapiello's novel Ayer no mas offers interesting material for the investigation of complex transgenerational relations affected by past traumatic experiences. The novel depicts the ways the descendants of the participants in the Spanish Civil War deal with their parents' guilt and shows how the memories of the past erupt after years of historical silence. The author, through references to postmemory and transgenerational transmission, attempts to explain the mechanisms behind inherited guilt, the connection between this guilt and the grief felt by the victims' families, and the way these experiences have influenced social life in contemporary Spain. Ayer no mas is an autofictional novel, and hence its analyses enable the examination of the approach of three generations of Spaniards to the traumatic past. The characters' experiences reveal that many years of historical silence that were supposed to facilitate forgetting in fact prevented the victims from ending their mourning and, at the same time, prevented the Spanish community from acknowledging the truth about the tragic past. As a result, both the descendants of the victims and the culprits suffer: the former because they have not been able to cope with the grief, and the latter because they have inherited the sense of guilt. Andres Trapiello attempts to heal those wounds with a narrative that addresses the hidden, yet sensed, history.
Keywords: Andres Trapiello; Ayer no mas; mourning; guilty; transgenerational transmission; postmemory